Does Ethnoscience Based STEM Improve Student Critical Thinking Skills Ability in Chemistry Learning? Meta-analysis - Hainun Musdalifah; Suyatmo; Sudrajat; Tomi Apra Santosa; Nenni Triana Sinaga (Postgraduate, University of Mataram, 2023)
The purpose of this study is to synthesize the effect of Ethnoscience-based STEM model size on students' critical thinking skills in chemistry learning. This type of research is a meta-analysis study. The research sample came from an analysis of 15 national and international journals that met the inclusion criteria. Data sources are accessed through Google Scholar, Wiley, ProQuest, ScienceDirect and Taylor of Francis.Â The data search keyword is the STEM model; Ethnoscience; The influence of ethnoscience-based STEM; and Students' critical thinking skills. Data analysis calculates the value of summary effect size or mean effect size with JASP. The results showed a positive influence of ethnoscience-based STEM models on students' critical thinking skills (Z = 8.685; p < 0.001). This finding explains that ethnoscience-based STEM models have a significant impact on students' critical thinking skills in chemistry learning with high categories (rE = 0.853).Â The ethnoscience-based STEM model provides solutions for teachers to encourage students' critical thinking skills in chemistry learning at school.